Developing a Numeracy Literacy Test Instrument on Halves and Quarter Fractions for Elementary School Students - Hafiziani Eka Putri; Nurfadillah Hasan; Indah Nurmahanani; Primanita Sholihah Rosmana (AL-ISHLAH: Jurnal Pendidikan, 2026)
Numeracy literacy is a fundamental competency in elementary education, yet existing assessments in Indonesian primary schools remain predominantly procedural and inadequately measure students’ conceptual understanding of fractions. This study aimed to develop and validate a numeracy literacy test instrument on halves and quarter fractions for second-grade elementary school students. This research employed a Research and Development (RD) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. Ten essay items were constructed based on numeracy literacy indicators and validated by two experts. Following expert review, one item was excluded, and the remaining nine items were piloted with 21 second-grade students from a public elementary school in Purwakarta, Indonesia. Item quality was analyzed using ANATES 4.0.5, including item validity, reliability, difficulty level, and discriminating power. Expert validation indicated that nine items were suitable for field testing after revision. Empirical analysis showed that seven items met all psychometric criteria, while two items were excluded because of insufficient validity and discriminating power. The final instrument demonstrated high reliability (r₁₁ = 0.84) and satisfactory item validity (rxy = 0.330–0.818). Item difficulty ranged from medium to very easy, whereas discriminating power ranged from very poor to good. The resulting seven-item instrument is psychometrically acceptable and suitable for assessing second-grade students’ numeracy literacy on fraction concepts. Although the findings provide preliminary evidence of validity and reliability, further validation with larger and more diverse samples is recommended to strengthen the instrument’s generalizability and broader educational applicability.